Recruitment and Job-Seeking Mechanisms for Zimbabwean Women Care Workers in the Domestic Services Sector in South Africa - Baison, Precious (African Human Mobility Review, 2021)
This article explores the migration of Zimbabwean women to South Africa toundertake various types of care work within the broader domestic work sector. Studieson care migration have largely discussed South to North migration flows. This isdespite evidence showing that there are significant flows of migrants within countriesin the Global South. This article seeks to understand the recruitment and job-seekingstrategies employed by women in this South-South migration flow in light of theirmigrant status and processes related to their migration. It is based on a qualitativestudy and utilizes data collected through semi-structured interviews conducted withkey informants from four domestic worker recruitment agencies and 23 care workersin two cities – Johannesburg and Pretoria. The leading findings were that Zimbabweanmigrant care workers in South Africa faced exploitative working conditions as themajority of them were undocumented or irregular. They faced challenges in obtainingvalid work visas and therefore, migrant care workers could not seek employmentthrough formal channels such as recruitment agencies. They used informal channelssuch as social networks and the ‘market’. The article discusses the implications of usingsuch strategies with regards to the subsequent working conditions and the protectionof care workers’ rights.